Influence of geometrical parameters of dental implants on secondary stability and osseointegration process depending on the type of bone - R. V. Studenikin; A. V. Sushchenko; A. A. Mamedov (Эндодонтия Today)
Aim. Comparison of the secondary stability and osseointegration rate of dental implants with fine and coarse threads placed in bones of various types.Materials and Methods. The study considered the data of 60 implants with fine and coarse threads, installed in the bone types I-III. After two and six months, an analysis of the loss of marginal bone, micromotion tests were carried out, changes in the stability coefficients were determined by the method of frequency magnetic resonance.Results. The 30 coarse threaded implants showed higher secondary stability compared to the finely threaded implants in all three bone types. Marginal bone loss was observed for both types of implants only in type III bone – but when comparing the absolute values, it is noticeable that they are smaller with large threads. Micromotion was absent in all cases for bone types I and II. For implants with large threads in type III bone, micromotion was less than 30 μm, and for implants with fine threads, it was 150-160 μm.Conclusions. High secondary stability is typical for implants installed in type I-II bone, regardless of the thread pitch, but the value of the stability coefficient is higher for specimens with coarse threads. In addition, there is no loss of marginal bone in these cases. Finely threaded implants placed in Type III bone are subject to micromovement.